A PENGEMBANGAN MEDIA COMIC BOOK UNTUK MENINGKATKAN KEMAMPUAN HOTS SISWA SEKOLAH DASAR PADA MATERI SISTEM PEREDARAN DARAH - Fira Faridatus Solihah; Asep Saefurohman; Mansur Mansur (Jurnal keilmuan dan Kependidikan dasar, 2023)
The purpose of this study was to determine the development procedures, feasibility and effectiveness of comic book learning media to improve HOTS abilities in class V science learning at SD Negeri Batuceper 1. This type of research is research and development with the ADDIE model through 5 stages namely Analysis, Design, Development, Implementation and Evaluation. Data collection techniques using interviews, questionnaires, test results and documentation. Data analysis techniques using descriptive qualitative and descriptive quantitative. Based on the results of the due diligence, the media expert obtained a percentage of 90.76% and the results of the due diligence of the material expert obtained a percentage of 91.66%, both of which were included in the very feasible criteria. The average result of the feasibility test obtained a percentage of 98.90% which was included in the very feasible criteria to be tested in the field. Meanwhile, the results of the effectiveness test using the results of the pretest and posttest tests in the field test to get a score 0.70 ≤ (g) ≤ 1.00 which is 0.82 included in the high criteria. Based on the results of the feasibility and effectiveness of comic book learning media to improve students' HOTS abilities, it is feasible and effective to be used in helping students' understanding, attracting students' attention and interest in learning and hone students' thinking skills in science learning at SD Negeri Batuceper 1 Tangerang City.